2009
DOI: 10.1016/j.exger.2009.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Bivalve models of aging and the determination of molluscan lifespans

Abstract: a b s t r a c tBivalves are newly discovered models of natural aging. This invertebrate group includes species with the longest metazoan lifespan approaching 400 y, as well as species of swimming and sessile lifestyles that live just for 1 y. Bivalves from natural populations can be aged by shell growth bands formed at regular intervals of time. This enables the study of abiotic and biotic environment factors (temperature, salinity, predator and physical disturbance) on senescence and fitness in natural popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 71 publications
2
84
1
1
Order By: Relevance
“…Similarly, in the oyster Crassostrea virginica with a maximal live span (MLSP) of only 6 years, not only antioxidant enzyme activity was lower but, the density of apoptotic and mitotic cells was also diminished in gill, adductor muscle and heart of mature compared to young oysters (Ivanina et al 2008;Sunila and LaBanca 2003). It would be interesting to see whether in short-lived scallops the reported shift in energy allocation from somatic maintenance towards reproduction at the end of life (see also Heilmayer et al 2004;Abele et al 2009) leads to reductions of cell proliferation in somatic tissues, and whether or not this is accompanied by a decline of apoptotic activity. On the other hand, low metabolic activity and sustained protection from oxidative damage over age, in combination with slow but continued cell turnover, presumably slow senescent decline in A. islandica.…”
Section: A Islandica (Gb)mentioning
confidence: 99%
“…Similarly, in the oyster Crassostrea virginica with a maximal live span (MLSP) of only 6 years, not only antioxidant enzyme activity was lower but, the density of apoptotic and mitotic cells was also diminished in gill, adductor muscle and heart of mature compared to young oysters (Ivanina et al 2008;Sunila and LaBanca 2003). It would be interesting to see whether in short-lived scallops the reported shift in energy allocation from somatic maintenance towards reproduction at the end of life (see also Heilmayer et al 2004;Abele et al 2009) leads to reductions of cell proliferation in somatic tissues, and whether or not this is accompanied by a decline of apoptotic activity. On the other hand, low metabolic activity and sustained protection from oxidative damage over age, in combination with slow but continued cell turnover, presumably slow senescent decline in A. islandica.…”
Section: A Islandica (Gb)mentioning
confidence: 99%
“…In rodents (Buffenstein et al 2008: measuring or reviewing data on catalase, SOD and methionine sulfoxide reductase) and birds (Cohen et al 2008: measuring uric acid, carotenoids, vitamin E and total antioxidant capacities), no predictable relationships between antioxidant levels and longevity is observed. Similar inconsistencies are observed in bivalves; Abele et al (2009) report elevated catalase levels compared to the shorter-lived bivalves while Ungvari et al (2011) found no difference in total or specific antioxidant capacities between long-lived A. islandica and shorter-lived Mercenaria mercenaria. Correspondingly, observations of SOD activity in the long-lived Margaritifera margaritifera (Fernández et al 2009) were very similar to those in the shorterlived Mytilus edulis (Winston et al 1990).…”
mentioning
confidence: 61%
“…Since Abele et al (2009) reviewed antioxidant capacities in bivalves, the field has considerably advanced, and if not dead, the role of oxidative stress in ageing is now severely questioned. One cannot take a component of the oxidative stress system in a species and make simplistic assumptions about its role in attenuated ageing, and there is no conclusive evidence that antioxidants play a significant role in determining lifespan in bivalves.…”
mentioning
confidence: 99%
“…Our work here highlights the need to have accurate demographic information on bivalve populations under study. As bivalves become increasingly utilized as models for aging research (Abele et al 2009) and biomonitoring (Byrne & O'Halloran 2001), it is essential to have an accurate grasp on what ''old'' is. The age structure at the sample site should be an important component in that process.…”
Section: Discussionmentioning
confidence: 99%
“…Bivalves are increasingly being used as new model organisms for the investigation of aging (Strahl et al 2007, Abele et al 2008, Abele et al 2009. To fully utilize bivalves in the investigation of aging and to be able to select suitable species for comparative investigations, it is necessary to obtain accurate information on the maximum life span of a species and their population growth parameters.…”
Section: Introductionmentioning
confidence: 99%